COVID-19 and liver - Rania S. Sobh; Sumaya H. El-Shazly; Samy Zaky; Nessren M. Bhaa EL-Deen; Mohamed Hassany; Lamiaa M. Kamal (The Egyptian Journal of Internal Medicine)
Abstract Background and aims The coronavirus disease 2019 (COVID-19) presents a significant health risk, affecting both healthy individuals and those with underlying health conditions, including liver diseases. This study aimed to evaluate the impact of COVID-19 on liver function in both hepatic and non-hepatic patients across varying degrees of disease severity, as confirmed by PCR testing. Methods In this prospective study, we included patients with confirmed COVID-19, both with and without liver conditions, who were admitted to the National Hepatology and Tropical Medicine Research Institute (NHTMRI) and Embaba Fever Hospital between November 2020 and July 2021. Results The study cohort consisted of 255 confirmed COVID-19 patients (mean age 52.16 years, 48.6% male, 24.3% with liver conditions). Among those with liver disease, 6.4% had mild symptoms, while 4.8%, 56.4%, and 33.8% experienced moderate, severe, and critical symptoms, respectively. Clinical characteristics were insignificantly different between hepatic and non-hepatic patients across the various COVID-19 severity grades, with the exception of the loss of taste and smell in severe cases and hepatic encephalopathy and oxygen saturation in critical cases. Laboratory findings similarly showed no significant differences, except that hepatic patients exhibited a notable decrease in platelet count and a significant increase in AST and bilirubin levels compared to non-hepatic patients. In critical COVID-19 cases, non-hepatic patients had significantly higher serum ferritin levels, while hepatic patients demonstrated increased serum bilirubin levels. Mortality was considerably higher in hepatic patients than in non-hepatic patients, particularly among those with severe and critical COVID-19. The study suggests that liver disease is associated with the progression to severe COVID-19, which includes a higher risk of mortality. Conclusion COVID-19 is linked to liver function impairment, with hepatic patients experiencing higher mortality rates compared to non-hepatic patients. Summary COVID-19, a novel coronavirus, presents a serious health threat to both healthy individuals and those with pre-existing health conditions. In this study, we evaluated its impact on individuals with liver disease compared to those without. The findings indicate that COVID-19 infection is associated with a decline in liver function and increased mortality rates in patients with liver disease.